(untitled) (Annals of Medical Research, 2021)
Aim: Today, smoking has become an epidemic that causes many health problems. One of the starting steps for individuals who want to quit smoking is the determination of the readiness level of the individual to quit. The aim of this study was to develop a measurement tool to determine the readiness levels of individuals who want to quit tobacco use.Material and Methods: This is a methodological study. For the context validity of the Readiness to Smoking Cessation Scale, the 120 item draft scale was sent to 4 expert physicians for their views. The construct validity of the draft scale was tested using the SPSS (Statistical Package for the Social Sciences) program running factor analysis tests (KMO, Bartlett test, Anti Image Correlation, Principal Components Analysis, Varimax Rotation)Results: A draft scale consisting of 28 items was formed from the pool of 120 items. Before explanatory factor analysis, principal components analysis on the non rotated components and principal components rotated on the principal axis were performed. The KMO of 0.853 at this point showed the high validity of our scale. Since the value attained was over 0.70, the scale was considered reliable. The Cronbach Alpha value of the scale was found to be 0.874. 10 items with total test correlation values under 0.45 were excluded from the scale. Conclusion: The RSC-Scale is a valid and reliable measurement tool with 18 items and 4 sub dimensions measuring the readiness of individuals to quit smoking. Through the RSC-S, the readiness levels of individuals who want to quit smoking can be determined, preventing loss of time and motivation as well as increasing costs.